Mathematik für die ersten Semester - Mückenheim, Wolfgang; Mückenheim, Wolfgang (De Gruyter Studium, 2015)
This book teaches what is known as higher mathematics – in other words, mathematics that extends beyond simple calculation, which is generally taught in the last years of high school and extended and learned in greater depth in the first semester of college study. It begins with an introduction to the language of mathematics and then covers the themes of arithmetic, algebra, geometry, and infinitesimal calculus.